Analysis of Students Misconceptions Using Instruments Three-Tier Diagnostic Test on Acid-Base Material - Chimayah, Mihlatal; Windayani, Neneng; Kurniasih, Nunung; Subarkah, Cucu Zenab; Sukmawardani, Yulia (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2025)
This research aims to analyze students' misconceptions using a three-tier diagnostic test on acid-base material. The type of research used in this research is descriptive research. This research was carried out at SMA Negeri 1 Muaragembong on class XI MIPA students. The data collection technique uses a multilevel multiple choice diagnostic test. The first level contains students' answers, the second level contains the reasons for the answers, and finally the level of belief. Data analysis was carried out by looking for the percentage of misconceptions from each concept in the acid-base material, namely the concept of acid-base theory, pH indicators of acid-base solutions, strength of acids and bases, as well as calculating the pH of acid and base solutions. The results of the research show that students' misconceptions about acid and base material using the three-tier diagnostic test instrument are divided into three, namely M1, M2 and M3. Based on the research results, the largest percentage of misconceptions regarding acid-base material is the misconception M1. Students with misconceptions M1 has a percentage of 30.96%, then the misconception M2 has a percentage of 14.63%, and misconceptions M3 has a percentage of 9.01%. Misconceptions M1 is a condition where students answer questions incorrectly at the first level and second level, but answer confidently at the third level. The causes of misconceptions that occur among students are due to incomplete reasoning, students' abilities, students' interest in learning and teachers' teaching methods.